MOTIVATION BEHIND THE FOREIGN EXPANSION OF ŁÓDŹ VOIVODESHIP COMPANIES - Grzegorczyk, Wojciech (Acta Scientiarum Polonorum. Oeconomia, 2019)
The aim of the article is to present the motivation behind foreign expansion of small and medium-sized enterprises (SMEs) based in Łódź Voivodeship. In order to carry out the project the researchers analysed the literature on the subject and conducted primary research on the sample of the selected companies with the use of survey and interview questionnaires that the managers of the companies surveyed responded to in 2017 and 2018.The decisions to enter foreign markets also resulted from the fact that companies wanted to increase their turnover and profits and in some cases, as the research proved, they were also motivated by factors concerning the companies productivity. Companies perceive foreign market expansion as an opportunity to expand their product offer, enter new markets, implement innovative solutions or achieve the previously set strategic goals, which is referred to as the so called strategic motivation.